The racial healing handbook : practical activities to help you challenge privilege, confront systemic racism & engage in collective healing - Singh, Anneliese A. (Social justice handbook series., 2019)
This handbook "offers powerful and practical tools to help you explore the history of racism, challenge stereotypes, and manage the stress and remorse that result from living in an unequal worlds. You'll understand your own racial identity, navigate daily and past experiences of racism, and examine ways racism affects all aspects of life-- from work to family to relationships. Finally, you'll discover how you can fight for racial justice, be an ally, and forge the building blocks needed to create a community of healing."--Cover.